FactCheck Q&A: does Australia have one of the highest progressive tax rates in the developed world? - Bain, K.; Hodgson, Helen (The Conversation, 2017)
The AiGroup's Innes Willox told Q&A that Australia has one of the highest progressive tax rates in the developed world. Is that true?